Effect of English proficiency on social capital and academic achievement among economic students - Hamzah, Muhammad Sodbir (Universiti Malaysia Sarawak, 2015)
The use of English language becomes increasingly important, either in educational sector or working sector.The role of social capital should be taken into consideration in helping the students to achieve their academic success. Previous findings indicated that students with limited use of English faced problems in advance subjects.Thus, this study examines the effect of English language proficiency towards social capital and academic achievement.This study employed the survey research design and the sample comprised of 81 undergraduate students enrolled in Economics courses from year two and three in Universiti Utara Malaysia (UUM). The instruments were adapted based on the constructs in the structural model developed.The data has been analysed using Structural Equation Modelling to enable simultaneous analysis of all the constructs and estimate the magnitude of the direct and indirect effects between the constructs.The findings show that there is a significant direct effect of English Language Proficiency (ELP) towards Academic Achievements (AA) and Social Capital Outside Family (SCOF), and from social capital outside family towards academic achievements.The mediating effect of social capital outside family towards English Language Proficiency (ELP) and Academic Achievement (AA) among economics students in UUM was significant.The findings suggest for more activities geared towards increasing students’ English language proficiency to help them to increase their academic achievements.